Acceptance of Golden Rice in the Philippine Rice Bowl - CHONG, Mark (Institutional Knowledge at Singapore Management University, 2003)
Few science issues in recent years have elicited such polarized public reactions as modern biotechnology and its agricultural applications. Although a new study conducted by the University of Illinois at Urbana-Champaign and the International Service for the Acquisition of Agri-biotech Applications (Ithaca, NY, USA) indicates that Southeast Asian stakeholders generally hold positive views about agricultural biotechnology.